Warthin tumor with extensive squamous and mucinous metaplasia: Pathologist's dilemma - J B Leena; Reshma G Kini; Sumanth Devaraju; Subhan R Ali (Wolters Kluwer Medknow Publications, 2014)
Secondary changes in Warthin tumor (WT) are not uncommon. Diagnostic error in Fine Needle Aspiration (FNA) is caused by a lack of typical features and the presence of individual atypical squamous cells in a necrotic background, mimicking carcinoma. Mucoepidermoid carcinoma, squamous cell carcinoma, and oncocytoma are the commonest tumors diagnosed in place of WT, the source of error being the presence of squamous metaplasia in the former two and the absence of the lymphoid cells in the latter. We report a case of WT with extensive squamous and mucinous metaplasia with desmoplasia and a certain degree of atypia which was diagnosed on FNA as Low Grade Mucoepidermoid Carcinoma (LGMEC). Prior FNA of the lesion may be the reason for the extensive metaplasia, desmoplasia, as well as atypia in our case. An extensive histopathological examination of the superficial parotidectomy specimen helped us arrive at the correct diagnosis.